Pit dewatering optimisation of a 3D FEFLOW unstructured groundwater model at geologically complex Antamina mine site in Peru - Dufour, R.M.; Aguirre, C.; Sanchez, M.; Maqueda, A.; Zwinger, J.M.; Renz, A.; Cho, J.; Evans, D. (Slope Stability 2020: Proceedings of the 2020 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2020)
Hydrogeological models are a simplification of reality and cannot incorporate all complexities which exist in nature. Modellers must decide on the level of detail necessary for a given problem based on the objective of the modelling exercise. Geology and structures play an important role in groundwater flow at mine sites in the Peruvian Andes (FloSolutions 2015). At the Antamina mine, flow is strongly controlled by faults, fracturing associated with bedding, folding and karstic features within limestone formations (Beal 2014). In addition, since Antamina is a skarn-type deposit, the intrusion has induced a complex geological system that governs the flow behaviour around the metamorphosised contact between the intrusion and the limestone host rock. This complexity makes the process of open pit dewatering and the evaluation of pore pressures for pit slope stability and geotechnical analysis challenging. Three-dimensional (3D) unstructured meshing in FEFLOW allows for an increased level of detail in the open pit and a better representation of the geological complexity and structures, at the same time allowing conservation of the 3D flow process at a regional scale with fewer mesh nodes in the numerical model and therefore, shorter simulation time. In addition to highlighting the new FEFLOW capabilities for unstructured meshes for pit dewatering; this paper presents innovative optimisation processes to minimise OPEX and CAPEX of the dewatering operation and a data fusion solution to significantly increase the accuracy of pore pressure simulation outputs for pit slope analysis.